Design Impact on Airflow Patterns in Fluidization Units - Renaudo, Carlos Alberto (2019)
The airflow behavior in a fluidization unit was integrally studied by means of experimental work and computational fluid dynamics simulation. The computational domain included the gas inlet pipe, plenum, perforated plate, fluidization chamber, and air outlet pipe. Different scenarios were simulated to allow distinguishing the best way to represent perforated-plate distributors and elucidate the impact of the grid design on the fluidization performance. The simulated pressure drop across the distributor and the plenum flow pattern were in concordance with the experimental data. It was found that the distance between the peripheral holes and walls has a great impact on the airflow downstream the distributor.